Beyond the Surface: A Chronic Polypoid Mass Over the Lower Back That Finally Spoke! - Shetty, Archana; Rao, Arjun; Kumar, Sharath; Muralidhar, Aparna; Sheik, Zeeshan (International Journal of Human and Health Sciences (IJHHS), 2025)
Nevus Lipomatosus Superficialis (NLS) is an uncommon benign hamartomatous lesion characterized by ectopic adipose tissue within the dermis. Accurate diagnosis relies on histopathology, as clinical features may overlap with other common benign cutaneous tumours having fibrous and adipose tissues. We report a case of a 60-year-old male who presented with a longstanding, asymptomatic, soft, skin-covered polypoid mass over the lower back. The lesion, present for fifty years had progressively enlarged in size over several years without associated pain or ulceration. Clinical examination revealed a soft, cerebriform mass with a wrinkled surface. Histopathological analysis demonstrated mature adipocytes embedded within the collagenous dermis, confirming the diagnosis of NLS. This case highlights the importance of considering NLS in the differential diagnosis of soft, cutaneous lesions in adults. Recognition of this entity is critical to prevent misinterpretation. Complete surgical excision remains the treatment of choice and has an excellent prognosis with low recurrence rates. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 265-268